Teachers’ Challenges in Conducting Online Teaching - Virgiyanti, Diska Fatima; Nuraini, Eka Indah; Fachriza, Aries; Dipta, Dinar; 'Aina Parahida, Tsaltsa Nakita (Universitas PGRI Madiun, 2023)
The spread of COVID-19 pandemic impacted to many factors, one of them is the education sector. For about 2 years, teaching and learning in all levels was done using an online system. As a result, school parties implemented new rules to support the education system during a pandemic. After Covid-19 is over, it appears that in the digital age, online learning has merged with other teaching and learning activities. This study sought to identify and characterize the difficulties teachers had when delivering online instruction and the methods they used to overcome those difficulties. For collecting the data, the researcher applied questionnaires and interviews as the research instruments. Then, the questionnaire's findings showed that teachers experienced difficulties in teaching online, including the use of technology, facilities, students’ motivation, and others.